Early Detection of Gadget Addiction in Teenagers Using Magnetic Resonance Spectroscopy with the Single Voxel - Novia Putri Tsania; Indah Sulistyowati; Brian Ilham Pranandya (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
Gadget addiction is one of the negative effects of excessive gadget use. Currently, there are many studies investigating internet addiction using a neuroimaging approach using diagnostic modalities. One of the modalities that can be used is Magnetic Resonance Imaging (MRI). One of the developments in MRI is the Magnetic Resonance Spectroscopy Imaging or MRS examination. MRS is a radiological examination that uses MRS supporting software in the MRI modality which can show correlations of anatomical and physiological metabolic or biochemical information present in the body, both in normal and abnormal conditions. The purpose of this study was to analyze the results of metabolite values in adolescents with suspected gadget addiction to prevent and support therapeutic research using MRS. The method in this study is descriptive qualitative research used to determine the results of metabolite values in adolescents with suspected gadget addiction to prevent and support therapeutic research using MRS with the single voxel. The sample used is teenagers with suspected gadget addiction. The result of the MRS examination can show the value of metabolites in the adolescent's body. The results of the MRS are in the form of graphs of metabolite values. Normal metabolite values will produce Hunter's Angle. The graph of teenagers with suspected gadget addiction does not form a Hunter's Angle. The values of NAA (5,49), Cho (3,63), Cr (3,65) and Glx (1.06) in adolescents with suspected gadget addiction decreased from the normal values of NAA (10-15), Cho (8), Cr (7) and Glx value (5-10).